Sugar beet and sugar market in European and national context - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
This paper aims to present the sugar beet and sugar market from a marketing perspective, both at national and european level, taking into account the main elements of the custom marketing mix on the sugar beet and sugar market (product, price, promotion, distribution) as well as the characteristics of demand and supply on the market of interest, represented by the consumption registered respectively by the number of economic agents and beet production at national level. We also want to show where we situated in Europe, in terms of the value of beet production at producer price. Once these issues have been analyzed statistically and interpreting the data gathered, the paper aims to highlight the strengths and weaknesses identified at market level by conducting a SWOT analysis.
Keywords: Q15; Q52; Q27; 330; sugar beet market; swot analyze; demand; supply